CULTURAL FACTORS IN LANGUAGE LEARNING – A STUDY ON CHILDREN OF MACEDONIAN ORIGIN IN SWITZERLAND - Selimi, Naxhi (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
This article presents selected results from a pilot study on the linguistic-cultural practices of students (N=18) of Macedonian origin in Switzerland and the influence of their parents’ linguistic-cultural attitudes on the writing skills of their children. The data collected in 2012 and 2016 by means of questionnaires, interviews and school texts form the basis for this. According to data, the Macedonian pupils surveyed in Switzerland do not succeed in closing the gaps in their writing skills of German as a second language in the course of their schooling and thus leave the nine-year elementary school with below-average written language skills. Their first language, Macedonian, on the other hand, shows a progression which is due to the support of parents, peers and, in particular, the teaching of Macedonian. Here, too, their language skills are below average. According to our data, positive language attitudes of parents without targeted school support from the outset are not sufficient to be successful in text writing.